Environmental pollution by carcinogenic benz(a)pyren and estimation of cleaning of drink water. jnfluence on morbility by malignant neoplasmes (Eurasian Journal of Ecology, 2016)
There are date about environmental pollution (water) of East-Kazakhstan, Pavlodar, Akmolinsk and North- Kazakhstan oblast by carcinogenic BP of class PAH . High maintenans BP, exceeding limity admitted concentration in 2-5 times wos revealed in water of opened and closed waterspings. Effective of clean constructions (on BP) is insufficiently. Control of this situation must be strengthen by official organization and produced modernization of clean construction.
Keywords: Environment; carcinogen; benz(a) pyren; clean constructions